Comprehensive Nutrient Gap Assessment (CONGA): A method for identifying the public health significance of nutrient gaps - Beal, Ty; White, Jessica M; Arsenault, Joanne E; Okronipa, Harriet; Hinnouho, Guy-Marino; Morris, Saul S (Nutrition reviews, 2021)
Abstract Identifying dietary nutrient gaps and interpreting their public health significance are essential for improving poor diets and reducing malnutrition. Evidence indicative of the burden of nutrient deficiencies and inadequate nutrient intake or availability exists in many countries yet is often misinterpreted or underused in decision-making. Clear guidance is lacking on how to synthesize and interpret the relevant evidence, which comes in many forms. To fill this methodological gap, an approach called Comprehensive Nutrient Gap Assessment was created to enable use of existing evidence to assess the public health significance of nutrient gaps and identify evidence gaps. Comprehensive Nutrient Gap Assessment requires ≥ 2 experts in nutritional assessment but does not require primary data collection or secondary quantitative data analysis. It can be implemented relatively quickly with low costs, for specific countries and subnational regions, and updated on the basis of new data with minimal effort. The findings from a Comprehensive Nutrient Gap Assessment are easily interpretable by nontechnical decision makers yet include clear justification for technical audiences.